Hubungan Transfusi Darah Berulang dan Kepatuhan Konsumsi Obat Kelasi Besi dengan Kadar Ferritin pada Pasien Thalasemia di Kota Depok - Kusumo, M. Kartono Wijoyo; Novita, Astrid; Hendarwan, Harimat (UIMA Press, 2024)
Repeated transfusions cause iron overload in β thalassemia patients. Therefore, iron chelation therapy is needed to reduce the amount of ferritin and ions in the blood. Compliance with iron chelation therapy is one of the factors that affect the patient's serum ferritin level. This study aims to determine the relationship between repeated blood transfusions and consumption of iron chelating drugs with serum ferritin levels of β thalassemia patients at Depok City Hospital in 2021. This research is a retrospective cohort study. The initial population was 112 people, sampling was carried out using the non-probability method and obtained 69 people who met the inclusion and exclusion criteria. This research was conducted from January 2021 to December 2021 in three medical record installations at Depok City Hospital. Respondents who rarely did repeated blood transfusions were 42 (60.9%), respondents who adhered to taking iron chelation drugs were 45 (65.2%), and respondents who had high ferritin levels were 43 (62.3%). There is a relationship between repeated blood transfusions and ferritin levels in thalassemia patients in Depok City in 2021. There is a relationship between adherence to taking iron chelating drugs and ferritin levels in thalassemia patients in Depok City in 2021. It is recommended that clinicians continue to provide a deeper understanding to parents or the patient's family to continue to carry out regular chelation therapy and check serum ferritin levels regularly.